Modeling of groundwater conservation zone using the modified GOD method on part of the southern slope of Merapi Volcano, Yogyakarta, Indonesia - Sejati, Sadewa Purba; Neritarani, Rivi (Journal of Degraded and Mining Lands Management, 2026)
Studying groundwater conservation zones is vital for maintaining groundwater sustainability. A model for groundwater conservation zones should be based on groundwater pollution vulnerability to ensure that groundwater resource sustainability addresses both quantity and quality. Still, few studies have been conducted on groundwater conservation zone models based on groundwater pollution vulnerability zones. This study used the modified GOD method to explore a groundwater conservation zone model based on groundwater pollution vulnerability zones. The research variables included groundwater depth, aquifer type, natural materials of the aeration zone, and land use. The data was collected through a field survey and literature reviews, and then processed using scoring and overlay techniques through geographic information system software. The results indicated that the modified GOD generated a model with better accuracy. The modified GOD produces a model of groundwater conservation priority zones with four classifications: groundwater conservation priority zone I is in areas with high pollution vulnerability; zones II and III are in areas with medium and low pollution vulnerability, respectively; and zone IV is in areas with no pollution vulnerability.